Uganda : Technical Assistance Report-Strengthening Cash Management and Reviewing the Treasury Single Account. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses recommendations for strengthening cash management and reviewing of the treasury single account in Uganda. The Cash Management Guidelines in Uganda have been approved. The coverage of the cash resource pool must be precisely defined and non-budget flows excluded. The cash flow forecasting model should continue to be developed along the lines given in previous Technical Assistance reports. The publication and dissemination of the Guidelines will provide authority to the Cash Policy Department to implement a program of training and capacity building within the central government entities in coordination with other directorates of the Ministry of Finance, Planning and Economic Development. This should be started as soon as the Guidelines are released.